Implementasi Blended Learning dalam Meningkatkan Motivasi Belajar Siswa - Kholil, Muhammad (ARZUSIN, 2022)
This study aims to provide an overview of the implementation of Blended Learning in increasing student learning motivation at MI Nurul Mun’in Karanganyar Paiton. This research uses a qualitative approach with the type of case study research conducted at MI Nurul Mun’in Karanganyar Paiton in Probolinggo for approIVimately 2 weeks. The data collection technique used observation and interview techniques, the observation technique used participant observation to students during the learning process both offline and online. Interviews were conducted with teachers, homeroom teachers and school principals. The application of blended learning in increasing students' motivation to learn can be said both students become more enthusiastic and enthusiastic in participating in lessons, making the class more effective and conducive, besides that the application of Blended Learning also helps students in improving their learning outcomes.